Reggie Watts disorients you in the most entertaining way (TEDx Patras, 2012)
: και δουλεύω και εργάζομαι. Με... Ένας άνθρωπος θα γνωρίζει και θα γνωρίζει και θα γνωρίζει. Δεν ξέρω. Με... Κάποιες φορές μπορούμε να δούμε, γιατί οι άνθρωποι εδώ κάνουν πράγματα, μπορούμε να φάμε. Με όταν είσαι σκληρός με κάποιον, δεν είναι το πρώτο φοράγμα. Και αυτό είναι ένας από τους πιο ευχαριστούμες σε αυτή την συμμετοχή. Δεν είναι τόσο πολύ, τόσο μικρό, σχετικά με ό,τι είναι όλα. Αλλά είναι μέσα στον εαυτό μας, για να καταλάβουμε την τοπογραφία των ζωών μας στον εαυτό μας. Το μέλλον δείχνει ότι δεν υπάρχει χρόνο, άλλα από την καταπληκτικότητα, από την αισθητία, από το μυαλό των μυαλών, στον οποίο ζούμε. Κοινωνική γνώση, αλλά σημαντική. Όταν αντιμετωπίζουμε φόβο σε αυτές τις φορές, και η φόβο βρίσκεται σε όλους μας, έχουμε και την αντιφόβο. Είναι δύσκολο να φανταστείς ή να μετρήσεις, αλλά η πραγματική ραδιασία είναι δύσκολα στατική, για να μπορείς να δεις μετά από την καθαρή σπρεκτρική αναλύση. Αλλά δείχνουμε, όμως, ότι υπάρχουν χρόνια που πολλοί από εμάς, αλλά σαν ένα hip-hop, όπως το Ted B Rock, έγινε μια τραγουδιά, και ελπίζω ότι δεχτείτε. Είναι μια τραγουδιά για τους ανθρώπους και οι σασκουάτσες και τα άλλα φιλικά φιλικά. Αυτή είναι η φιλική φιλικά. Ας πάμε. I've been trying to look around and I've been trying to find myself but every time it gets me wrong there is nothing saying your way. I've been trying to be the one that you believe in and every moment I wanna be so, so safe and every one I want to see I'm bound to burn and you can do anything as long as you don't hurt or along the way. I've been looking around and I wanna tell you what is wrong with me cause if you were to walk and I'd say you're sorry and I'd say I got your love and I got no one for me so I won't give you one for me I won't back out, I won't back out, I won't back out the way and it's like, you know, you can use as many of those things that you want, right? And the computer models, no matter how many that you have and how many people that you use are never going to be able to arrive at the same conclusions. Four years ago I worked with a few people at the Brookings Institute and I arrived at a conclusion. Tomorrow is another day. Not just any day, but it is a day. It will get here. There's no question. And the important thing to remember is that this simulation is a good one. It's believable. It's tactile. You can reach out, things are solid. You can move objects from one area to another. You can feel your body. You can say I'd like to go over to this location and you can move this mass of molecules through the air over to another location at will. That's something you live inside of every day. Now with the allocation and the understanding of the lack of understanding, we enter into a new era of science in which we feel nothing more than so much so as to say that those within themselves, comperary or non-comperary, will figuratively figure into the folding of our non-understanding and our partial understanding into the networks of which we all draw our source and conclusions from. So, as I say before the last piece, feel not as though it is a sphere we live on, rather an infinite plane which has the illusion of leading yourself back to the point of origin. Once we understand that all the spheres in the sky are just large infinite planes, it will be plain to see. This is my final piece. And just remember, everything you are is more important to realize the negative space as music is only the division of space and it is the space we are listening to divided as such which gives us the information in comparison to something other that gives us the idea of what the idea that wants to be transmitted wants to be. So, please, without further ado. Thank you. Alright, this is a fun one. It goes like this. . Okay, now for the last piece I'd like to do, this one goes very similar to this. I hope you guys recognize it. Here we go. Okay, that still works. Okay, good. Alright, here we go. . Here we go. . . Thank you. Enjoy the rest. Thank you. .